Seeing tongues, hearing scripts : orality and representation in the ancient novel - Rimell, Victoria (Eelde : Barkhuis Publishing ; Groningen : Groningen University Library, 2007)
The Greek and Roman novels can be seen as an important transitional moment in the trajectory from performance to reading, from oralism to textuality, that has underpinned the history of discourse in European consciousness since the 5th century BC. In different and intriguing ways, they explore the contrast, tension, conflict, competition or dialogue between modes of discourse, which frame the novel's concern with identity and self-fashioning, as well as advertising innovation more generally. This volume brings together an international group of scholars interested in ancient and modern construc.
Introduction / Victoria Rimell, editor -- Orality and authority in Xenophon of Ephesus / Jason Konig -- Omero e la sibilla. Mimesi e oralita nella Cena Trimalchionis / Andrea Cucchiarelli -- The inward turn: writing, voice and the imperial author in Petronius / Victoria Rimell -- Visualising drama, oratory, and truthfulness in Apuleius Metamorphoses 3 / Regine May -- Vocis immutatio: the Apuleian Prologue and the pleasures and pitfalls of vocal versatility / Wytse Keulen -- The ass's ears and the novel's voice. Orality and the involvement of the reader in Apuleius' Metamorphoses / Luca Graverini -- Advertising one's own story. Text and speech in Achilles Tatius' Leucippe and Clitophon / Marko Marincic -- La voix et la main: la lettre intime dans Chereas et Callirhoe / Patrick Robiano -- Poiein aischra kai legein aischra, est ce vraiment la meme chose? Ou la bouche souilee de Chariclee / Romain Brethes -- 'Novels in the Greek letter': Inversions of the written-oral hierarchy in the Briefroman 'Themistocles' / Owen Hodkinson -- Divine episemology: the relationship between speech and writing in the Aithiopika / Kathryn Chew -- Fixity and fluidity in Apollonius of Tyre / Stelios Panayotakis -- List of contributors -- Indices.
Met lit.opg., index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
eBooks on EBSCOhost
Keywords: Classical fiction -- History and criticism; Orality in literature; Written communication; Greece -- Civilization; Rome -- Civilization; Roman ancien -- Histoire et critique; Oralité (Psychanalyse) dans la littérature.; Communication écrite.; Grèce -- Civilisation; Rome -- Civilisation; LITERARY CRITICISM -- Ancient & Classical; HISTORY -- Ancient -- General; Civilization; Classical fiction; Orality in literature; Written communication; Greece; Rome (Empire); Romans; Klassieke talen; Mondelinge literatuur; Tekstoverlevering; Schriftelijke communicatie; Criticism, interpretation, etc